RESPON PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L.) VARIETAS SULUTTAN UNSRAT 1 DENGAN METODE SRI TERHADAP PEMBERIAN PUPUK ANORGANIK DAN PUPUK HAYATI - Ratela, Leonardie W.; Polii-Mandang, J. Sh.; Paulus, J. M. (Universitas Sam Ratulangi, 2016)
ABSTRACTÂ This research aims tostudythe response of growth and yield of paddy rice to the combination of inorganic fertilizer and biological fertilizers. The design of experiments used in this study is a single factor in a completely randomized design (CRD), which consists of 5 treatments and repeated 5 times with the treatment as follows: P0 = 100% NPK (control) P1 = 100% NPK + 100% Biofertilizer Petrobio, P2 = 75% + 25% NPK Fertilizer Biological Petrobio, P3 = 50% + 50% NPK Fertilizer Biological Petrobio, P4 = 25% + 75% NPK Fertilizer Biological Petrobio. Giving Phonska inorganic fertilizer mixed with the biological fertilizer petrobio influence on the growth and yield of rice varieties Suluttan Unsrat I. Treatment NPK fertilizer Phonska 75% and 25% of biological fertilizers petrobio produce an average plant height is 98.40 cm high, 24.40 cm panicle length , Total grain permalai 167 grains, grain pithy permalai Total 155.20 grains and weight of 1000 grains contain.Key words: rice paddy fields, of SRI (System of Rice Intensification), inorganic fertilizers, biofertilizers